2020
DOI: 10.1186/s12967-019-02188-9
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation deficiency of lipopolysaccharide-binding protein and corticosteroid-binding globulin associated with activity and response to treatment for rheumatoid arthritis

Abstract: Background: Serum protein glycosylation is an area of investigation in inflammatory arthritic disorders such as rheumatoid arthritis (RA). Indeed, some studies highlighted abnormalities of protein glycosylation in RA. Considering the numerous types of enzymes, monosaccharides and glycosidic linkages, glycosylation is one of the most complex post translational modifications. By this work, we started with a preliminary screening of glycoproteins in serum from RA patients and controls. Methods:In order to isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
0
4
1
Order By: Relevance
“…However, it has been shown that neither LBP nor MyD88 are solely regulated at the level of mRNA expression and also in dependence of different ligands/ compounds (e.g. endotoxin, peptidglycane and proinflammatory cytokines) [67][68][69][70]. Difference between the studies of Cariello et al [62] and our study might have resulted from differences in the composition of the oils used but may also be related to difference in the models (e.g.…”
Section: Plos Onecontrasting
confidence: 58%
“…However, it has been shown that neither LBP nor MyD88 are solely regulated at the level of mRNA expression and also in dependence of different ligands/ compounds (e.g. endotoxin, peptidglycane and proinflammatory cytokines) [67][68][69][70]. Difference between the studies of Cariello et al [62] and our study might have resulted from differences in the composition of the oils used but may also be related to difference in the models (e.g.…”
Section: Plos Onecontrasting
confidence: 58%
“…In addition, current medical practice suggests an increasingly personalised medicine. Thereby, more and more studies, such as ours, are investigating molecules of interest that can guide the therapeutic process, often derived from promising studies in the broad field of rheumatoid arthritis [32][33][34] that could inspire further future studies in JIA. Furthermore, it has recently been shown that sCal can be easily and rapidly detected in blood using a lateral flow immunoassay-based technology, which may provide a useful point-of-care testing.…”
Section: Rmd Open Rmd Open Rmd Openmentioning
confidence: 99%
“…Protein markers are subject to intricate regulatory mechanisms, encompassing post-translational modi cations and protein interactions. These complexities render their precise and sensitive detection and quanti cation challenging, particularly in the initial phases of a disease [31,32]. On the contrary, RNA markers can detect early changes in cells or tissues and are often more reversible, rendering them advantageous for assessing treatment e cacy and monitoring disease progression [33].…”
Section: Discussionmentioning
confidence: 99%